(-4xy^3)*(-xy)+(-3xy^2)^2
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 01:17:47
(-4xy^3)*(-xy)+(-3xy^2)^2(-4xy^3)*(-xy)+(-3xy^2)^2(-4xy^3)*(-xy)+(-3xy^2)^2解原式=4x²y的4次方+9x²
(-4xy^3)*(-xy)+(-3xy^2)^2
(-4xy^3)*(-xy)+(-3xy^2)^2
(-4xy^3)*(-xy)+(-3xy^2)^2
解
原式
=4x²y的4次方+9x²y的4次方
=(4+9)x²y的4次方
=13x²y的4次方
原式=(-4xy)·y²·(-xy)+9x²y⁴
=4x²y²·y²+9x²y⁴
=4x²y⁴+9x²y⁴
=13x²y⁴
(-3xy+2xy)-(4xy+xy)
3xy-4xy-(-2xy)
4xy+6xy-3xy=?
3xy-4xy-(-2xy)
xy×(xy)²-3xy
.(3xy²)²+(-4xy³)(-xy) (3xy²)²+(-4xy³)(-xy)
(-4xy^3)×(-xy)+(-3xy^2)^2
(-3xy^2)^2+(-4xy^3)*(-xy)=多少
(-4xy^3)*(-xy)+(-3xy^2)^2
(3xy^2)^2+(-xy^3)(4xy)
计算-xy-(4z-2xy)-(3xy-4z)
-xy(4z-2xy)-(3xy-4z) 化简
计算:3xy-4xy-(-2xy)要过程
(1)3xy-4xy-(-2xy)
(-4xy³)(-xy)+(-3xy²)²
3xy-4xy-(-2xy)的解法
3xy-4xy-(-2xy) 快啊,亲
3xy-3xy-xy+2yx